Effect of company and corporate governance characteristics on audit pricing during recession period: A UK sample - HUANG, Zhaolong (2012)
This paper investigates the effect of company characteristic and the quality of corporate governance (CG) on audit fee during recession period in UK. Data on 160 listed companies in FTSE 350 are sampled for favourable, recession and post-recession period in the dissertation. The relations between fees and variables such as ROA, total assets, number of subsidiary, and the ratio (AR and Inventory) /total assets are agreed with previous literature. For liquidity, leverage, and the existence of loss, there are differences with the existing literature. The paper also examine the influence of quality of corporate governance on audit pricing and using a new composite measure comprising profit effectiveness, director utilization and employee utilization. I found that after controlling for board of director characteristics, there is a significant negative association between the overall quality of CG and audit fee. The results also indicate that effective employee management has lower audit fees for all period, especially in the favourable period. Contrary to my expectation, I find the association between profit effectiveness and audit pricing is positive and significant during recession period. In addition, this paper demonstrated that these change of economic condition have an impact on the relationships between audit fees and company and corporate governance characteristics. It also proven that the recession has a negative effect on audit fee in UK and it probably due to the effect of changing audit fee benchmark on audit pricing during recession.